Mathematical model of elements of automated system of loose materials dosing - Kozak, Andriy (Publishing House of Lviv Polytechnic National University, 2016)
Automatic dosing system for loose materials is widely used in construction, food and pharmaceutical industries to prepare various mixtures. The main criterion for optimization of such systems is the accuracy of dosing of each component of the mixture, which depends on the speed component dosing and other process factors. Technological requirements for product quality in production and the high cost of individual components of the mixture strictly regulate the developers of the automated system loose materials size dosing errors. Ensuring compliance with the maximumpossible mix recipe requires dosing of each component with high accuracy, which is a daunting task for engineers. Precision dispensing in automated systems is a function of the large number of systematic and random factors: size, shape and relative position of individual particles of the material; coupling coefficient of each other and of the structural elements of the dispenser; relative humidity of material dosage and indoor air; the height of the fall of the material in the receiving container; the value of the dispenser tilt to a level of horizon; electromechanical vibration and noise, etc. Developed simulation model of frequency-controlled electric screw feeder that is different from the known one facts that modeling of screw feeder is considering mass “falling pillar” which is constantly changing as the accumulation of material in the hopper.